PENGARUH KONTEN “POLDA RIAU MENYAPA” PADA FANPAGE FACEBOOK TERHADAP PEMENUHAN INFORMASI PUBLIK - Saras Aulora; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The development of information technology and social networking media or social media affects the patterns of media workers in finding ideas, information and news sources. Social media can also be used as a source of news. The social media that is most often and considered effective in finding news ideas and sources is Facebook. In delivering information, the Riau Police Public Relations utilizes the Facebook fanpage which contains the most current information. This method is considered effective in meeting the needs of public information. This study uses the Stimulus-response theory which assumes that verbal (spoken-written) words, non-verbal cues, pictures and certain actions will stimulate others to respond in a certain way and the New Media Theory that focuses on media to be able to increase social interaction between humans through several social networks.The method used in this research is an explanative quantitative method. The population in this study were followers of the Facebook fanpage of Bid Humas Riau Police with 100 respondents. The data collection technique used purposive sampling technique and questionnaire. And for data processing, the questionnaire test was carried out using Windows version 16 of the Statistical Product and Service Solution (SPSS) program.The results showed a significance value of 0.000, smaller than α = 0.05 with the regression equation Y = 2.464 + 0.840 X. In addition, the value of tcount 13.467> ttable 1.984. Thus Ha in this study was accepted, while Ho was rejected. The correlation coefficient value obtained is 0.806 and the coefficient of determination is 64.9%. The content of "Polda Riau Menyapa" can affect the fulfillment of public information, and the remaining 35.1% is influenced by variables or other factors not examined in this study. Keyword : Fanpage facebook, Public information, Stimulus-response